2007
DOI: 10.2215/cjn.03951106
|View full text |Cite
|
Sign up to set email alerts
|

Screening, Diagnosis, and Treatment of Depression in Patients with End-Stage Renal Disease

Abstract: Depression is common in patients with end-stage renal disease and has been linked to increased mortality. Screening for depression in the general medical population remains controversial; however, given the high prevalence of depression and its significant impact on morbidity and mortality, a strong case for depression screening in patients with end-stage renal disease can be made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
169
1
7

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 200 publications
(181 citation statements)
references
References 90 publications
4
169
1
7
Order By: Relevance
“…2,3,34,120,121 Pharmacologic options to treat depression include selective serotonin reuptake inhibitors (SSRIs), as well as the newer selective serotonin and norepinephrine reuptake inhibitors. 24,34,115,[122][123][124][125] Other agents such as tricyclic antidepressants, monoamine oxidase inhibitors, and St. John's wort should be avoided if possible because of potential exacerbation of common adverse events in dialysis patients, including drug-drug interactions, arrhythmias, and orthostatic hypotension. 24,115,122,125 Patients who receive these antidepressant medications should be closely monitored for development of a prolonged corrected QT interval.…”
Section: Anxietymentioning
confidence: 99%
See 3 more Smart Citations
“…2,3,34,120,121 Pharmacologic options to treat depression include selective serotonin reuptake inhibitors (SSRIs), as well as the newer selective serotonin and norepinephrine reuptake inhibitors. 24,34,115,[122][123][124][125] Other agents such as tricyclic antidepressants, monoamine oxidase inhibitors, and St. John's wort should be avoided if possible because of potential exacerbation of common adverse events in dialysis patients, including drug-drug interactions, arrhythmias, and orthostatic hypotension. 24,115,122,125 Patients who receive these antidepressant medications should be closely monitored for development of a prolonged corrected QT interval.…”
Section: Anxietymentioning
confidence: 99%
“…24,34,115,[122][123][124][125] Other agents such as tricyclic antidepressants, monoamine oxidase inhibitors, and St. John's wort should be avoided if possible because of potential exacerbation of common adverse events in dialysis patients, including drug-drug interactions, arrhythmias, and orthostatic hypotension. 24,115,122,125 Patients who receive these antidepressant medications should be closely monitored for development of a prolonged corrected QT interval. 126,127 If this complication occurs, the antidepressant medication should be discontinued.…”
Section: Anxietymentioning
confidence: 99%
See 2 more Smart Citations
“…However, Craven et al (1988) found that only 8.1% met Diagnostic and Statistical Manual, Third Edition, criteria for major depression. Kimmel and colleagues reported that among outpatients who were treated with HD, approximately 25% of them were depressed, with mean BDI scores that corresponded to mild levels of depression in the general population (Cohen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%